Digestibility and nitrogen utilisation of diets containing protein at different levels and supplemented with DL-methionine, L-methionine and L-lysine in blue fox (Alopex lagopus) - Dahlman, Tuula; Kiiskinen, Tuomo; Mäkelä, Jaakko; Niemelä, Paavo; Syrjälä-Qvist, Liisa; Valaja, Jarmo; Jalava, Taina (Elsevier, 2002)
v 2002 ok